2016
DOI: 10.1111/jgs.14129
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Interventions in Six Dimensions of Wellness That Protect the Cognitive Health of Community‐Dwelling Older Adults: A Systematic Review

Abstract: Intellectual and physical interventions were most studied, with varied results. Future research is needed using more-consistent methods to measure cognition. Researchers should include the National Institutes of Health Toolbox Cognition Battery among measurement tools to facilitate effective data harmonization, pooling, and comparison.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…Moreover, holistic wellness may have particular relevance for gerontology practitioners (Strout et al, 2016). The construct could be useful when clinicians seek a holistic assessment of an older person's well-being.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, holistic wellness may have particular relevance for gerontology practitioners (Strout et al, 2016). The construct could be useful when clinicians seek a holistic assessment of an older person's well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Others have suggested that holistic wellness, a characteristic more commonly studied in young adults, may be a useful paradigm to measure healthy aging (e.g. Strout et al, 2016).…”
Section: Background and Objectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…Our subjects may also be physically active, which studies have shown to have a positive influence on cognitive function by stimulating neurogenesis and benefit brain plasticity in older populations. [3638] However, the complexities and mechanism of neurobiological rehabilitation may be better understood in further studies. [39,40] Our results may not apply to individuals with poorer cognitive or motor functioning.…”
Section: Discussionmentioning
confidence: 99%